Feasibility of Prehabilitation Prior to Breast Cancer Surgery: A Mixed-Methods Study - Brahmbhatt, Priya; Sabiston, Catherine M.; Lopez, Christian; Chang, Eugene; Goodman, Jack; Jones, Jennifer; McCready, David; Randall, Ian; Rotstein, Sarah; Santa Mina, Daniel (Frontiers in Oncology, 2020)
Background: Breast cancer surgery results in numerous acute and long-term adverse outcomes; the degree to which these can be mitigated or prevented through prehabilitation is unknown.We conducted a longitudinal, single-arm, mixed methods study to examine the feasibility of prehabilitation in 22 women undergoing breast cancer surgery. All participants received an individualized exercise prescription including upper quadrant-specific resistance and mobility training and aerobic exercise for the duration of their surgical wait time. Feasibility was assessed by recruitment, adherence, attrition, and intervention-related adverse event rates. An exploratory investigation of intervention efficacy was conducted via six-minute walk test, upper quadrant strength and range of motion, volumetric chances associated with lymphedema, and participant-reported quality of life, fatigue, pain, and disability. Outcome assessments were conducted at baseline, prior to surgery, and at six-and 12-weeks after surgery. Semi-structured interviews with a sub-set of participants (n=5) and health care providers (HCPs; n=2) were conducted to provide further insights about intervention feasibility. Qualitative data were analyzed using a hybrid inductive and deductive thematic analysis approach.Results: Recruitment and attrition rates were 62% and 36%, respectively. Average prehabilitation duration was 31 days (range= 7-69 days). Seventy six percent of participants complied with at least 70% of their prehabilitation prescription. There was a clinically significant increase in the sixminute walk distance from baseline to the pre-operative assessment (57 meters, 95%CI = -7.52,121.7). The interviews revealed that the intervention was favourably received by participants and HCPs, and included suggestions that prehabilitation: i) should be offered to all surgical candidates; ii) is an avenue to regain control in the pre-operative period; iii) is a facilitator of postoperative recovery; and iv) is an opportunity to provide education regarding post-operative rehabilitation protocols. A preference for multimodal prehabilitation (including dietetic and psychological counselling) was also highlighted.Our findings suggest that surgical prehabilitation in women with breast cancer is feasible. Data are hampered by study sample size and lack of a control group. Thus, randomized controlled trials to examine prehabilitation efficacy in people with breast cancer, especially interventions employing a multimodal strategy, are warranted.